Chronic Alcohol Treatment-Induced GABA-Aα5 Histone H3K4 Trimethylation Upregulation Leads to Increased GABA-Aα5 Expression and Susceptibility to Alcohol Addiction in the Offspring of Wistar Rats - Zeng, Kuan; Xie, Aimin; Zhang, Xiaojie; Zhong, Baoliang; Liu, Xuebing; Hao, Wei (Frontiers in Psychiatry, 2018)
GABA-Aα5 is considered to be associated with alcohol-induced memory deficits. However, whether it participates in the formation of alcohol addiction or regulation of its susceptibility is unknown. Here, we used a chronic alcohol treatment model to obtain alcohol-addicted Wistar rats. Long-term alcoholism increased the expression of PFC GABA-Aα5 by inducing its histone H3K4 trimethylation, and these changes could be hereditary and lead to increased vulnerability to alcohol addiction in offspring. This study indicates the risk of long-term alcoholism in future generations, emphasizes the importance of GABA-Aα5 in the formation of alcohol addiction and the regulation of its susceptibility, and provides new evidence regarding the mechanisms underlying alcohol addiction.